Core–shell structured Li–Fe electrode for high energy and stable thermal battery. Issue 8 (9th February 2022) - Shin, Jaewook; Kang, Hyeonmuk; Lee, Yongju; Ha, Sang Hyeon; Cho, EunAe
Abstract : In LiFE, higher Li content can lead to higher energy output but increases the risk of Li leakage. Here, we demonstrate a novel core–shell electrode structure to achieve a higher energy output and prevent the Li from leakage. Abstract : The thermal battery, a key source for powering defensive power systems, employs Li alloy-based anodes. However, the alloying increases the reduction potential of Li which lowers the overall working voltage and energy output. To overcome these issues, Li alloy must be replaced with pure Li. Utilizing pure Li requires a structure that can hold liquefied Li because the working temperature for the thermal battery exceeds the melting point of Li. The liquefied Li can leak out of the anode, causing short-circuit. A Li–Fe electrode (LiFE) in which Fe powder holds liquefied Li has been developed. In LiFE, higher Li content can lead to higher energy output but increases the risk of Li leakage. Thus, Li content in the LiFE has been limited. Here, we demonstrate a novel core–shell electrode structure to achieve a higher energy output. The proposed core–shell LiFE incorporates a high Li content core and a low Li content shell; high energy comes from the core and the shell prevents the Li from leakage. The fabricated core–shell structured electrode demonstrates the high energy of 9074 W s, an increase by 1.66 times compared to the low Li content LiFE with the conventionally used Li content (5509 W s).